Theoretical-methodological foundations of nursing training aimed at self-care in patients with intellectual disabilities - María del Rosario Melo Muñoz; Ángel Luis Gómez Cardoso; Elizabeth Gómez Núñez; Rolando Rodríguez Puga (Medisur)
Patients with intellectual disabilities often show support needs, in response to which nursing professionals must direct actions that allow to improve the life quality. To put these activities into practice, the patient must possess innate or acquired skills that will be perfected through specialized assistance. The objective of the research is to present the theoretical-methodological foundations of nursing training aimed at self-care in patients with intellectual disabilities. A search of scientific literature was carried out on the Internet. The examined articles correspond to journals indexed in Scopus, SciELO, Redalyc, DOAJ and Latindex. 58 texts were obtained and the research was defined by the 30 that met the inclusion criteria. Self-care should be a priority for all people, including those with intellectual disabilities, since in most cases they require special care. Patients must be able to overcome daily challenges, achieve independence and understand the importance of health care. For this reason, training, guidance and support from nursing care effectively promotes the social inclusion of these people. Self-care in patients with intellectual disabilities from nursing care is essential, since mental and emotional well-being directly influences the health status of the individual.